ChemInform Abstract: Natural Supramolecular Protein Assemblies. Issue 6 (21st January 2016) - Pieters, Bas J. G. E.; van Eldijk, Mark B.; Nolte, Roeland J. M.; Mecinovic, Jasmin
Abstract: Review: structural and functional studies on a diverse set of natural supramolecular protein assemblies; 51 refs.